2021
DOI: 10.3389/fpsyg.2020.564112
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Climate(s), Distributed Leadership, and Work Outcomes: The Mediating Role of Organizational Identification

Abstract: Organizational identification (OI) has increasingly attracted scholarly attention as a key factor in understanding organizational processes and in fostering efficient human resource (HR) management. Available evidence shows that organizational ethical climate crucially predicts OI, a key determinant of both employees’ attitudes and behaviors. In the present paper, we examined the relationship between two specific ethical climates (self-interest vs. friendship), distributed leadership (DL), and employees’ attit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 86 publications
2
26
0
1
Order By: Relevance
“…Finally, further variables that we have not considered might have an impact on job performance and a role in our mediation model. Future research could test the effect of work characteristics (e.g., occupation type, income levels, job security, leadership style) and organization-based attitudes (e.g., trust in the organization, organizational identification) on job performance, and include possible moderators like job content (in the perspective of TP), and organizational culture (in the perspective of OCB) [ 77 , 78 , 79 , 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, further variables that we have not considered might have an impact on job performance and a role in our mediation model. Future research could test the effect of work characteristics (e.g., occupation type, income levels, job security, leadership style) and organization-based attitudes (e.g., trust in the organization, organizational identification) on job performance, and include possible moderators like job content (in the perspective of TP), and organizational culture (in the perspective of OCB) [ 77 , 78 , 79 , 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…Social identity is a part of an individual's self-concept, which comes from the individual's perception of being a member of a social group, and sharing certain values with the group and its members. As part of a particular social group, employees also identify with their groups or organizations accordingly, which represents their acceptance of the organization's value and promises their organizational commitment in the future (Barattucci et al, 2021). Lee et al (2015) concluded in their meta-analysis that OID exists as the basis for general attitudes and behaviors in organizations.…”
Section: The Positive Impact Of Psychological Capital On Job Satisfactionmentioning
confidence: 99%
“…Research has proven that organizational identification has a positive effect on job satisfaction, and organizational commitment behaviors. A variety of studies have established that organization and environment level factors, such as organizational climate, perceived support from the organization, and the autonomy of the job contribute to employees' organizational identification (Edwards and Peccei, 2010;Salvatore et al, 2018;Barattucci et al, 2021). However, little attention has been paid to the intrinsic positive power of individuals that can impact on organizational identification.…”
Section: Introductionmentioning
confidence: 99%
“…Leadership literature identifies the impact of leadership on the success and management of the project; however, there is a deficient understanding of the project-based organizations (Albert et al, 2017 ). In the past three decades, the researcher and practitioners are interested in the psychological relationship between employees and their organizations (Barattucci et al, 2021 ). Research calls to explore the underlying mechanism through which leadership styles influence information system development (ISD) projects.…”
Section: Introductionmentioning
confidence: 99%